6. Hyperventilation increases brain connectivity in healthy subjects and in focal cryptogenic epileptic patients. Issue 1 (January 2015) - Mazzucchi, E.; Vollono, C.; Losurdo, A.; Testani, E.; Gnoni, V.; Di Blasi, C.; Giannantoni, N.M.; Lapenta, L.; Brunetti, V.; Della Marca, G.
<x xml:space="preserve">Abstract</x> Hyperventilation is a widely used EEG activation method. Aim of the study was to evaluate the modifications in brain connectivity due to hyperventilation in normal subjects and in cryptogenic focal epileptic patients. We examined EEG recordings from 19 scalp electrodes of 22 normal subjects and 22 focal cryptogenic epileptic patients. Exclusion criteria were: migraine, cerebrovascular disease, MRI abnormalities and use of drugs, apart from Antiepileptic drugs in epileptic group. We selected segments before (PRE), during (HYPER) and five minutes after (POST) hyperventilation. We analyzed neural generators through low resolution electromagnetic tomography (sLORETA) for the following bands: delta (1–4 Hz), theta (5–7 Hz), alpha (8–13 Hz), beta (14–30 Hz) and gamma (31–60 Hz). We also computed EEG lagged coherence between 19 Regions Of Interest for the same bands. Finally, we performed intergroup analysis of Mean Lagged Coherence. In both groups hyperventilation significantly increases EEG (p < 0.01), particularly in posterior cingulate cortex, and lagged coherence (p < 0.01). Intergroup analysis of mean lagged coherence showed significant differences between the two groups (p < 0.001). Our findings demonstrate that hyperventilation is associated with activation of posterior cingulate cortex. Moreover it increases brain connectivity, with significant differences between healthy subjects and focal cryptogenic epileptic patients.